Tingkat Kepuasan Pasien Poli Umum Terhadap Waktu Pelayanan di Puskesmas Maniangpajo - A. Muh. Akbar Jaya (YICI Publisher, 2024)
The quality of service from a health center is one of the factors that will make patients come back for treatment or even leave for life. In the current era, health centers are required to improve the quality of service and the comfort of patients who come for treatment, the problem that occurred at the maniangpajo health center was a decrease in the number of patient visits in the 2020-2022 period, the results of observations and initial interviews before the study, there were three main problems that caused a decrease in visits, namely the time of the executor, The study aims to find out the factors that affect the level of patient satisfaction of the general clinic of the maniangpajo puskesmas for the period January-June 2023This study is a cross-sectional study, data were collected through distributing questionnaires given to 94 respondents, interviewing infomans, namely the head of the puskesmas, general practitioners and patients, observation and document review were carried out by researchers so that conclusions were drawn.The results of the study indicate that there are efforts to improve health services by the maniangpajo puskesmas, this is based on a comparison of the results of the public service satisfaction survey in 2021 and 2023, namely the implementation time indicator of 78.7% (satisfactory), the behavior of the implementer of 72.7% (satisfactory) and facilities and infrastructure of 70.7% (satisfactory).